1989
DOI: 10.1002/bjs.1800760509
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after choledochojejunostomy for bile duct stones with complex clearance of the bile duct

Abstract: In this retrospective study, the long-term follow-up of patients undergoing choledochojejunostomy (Roux-en-Y) for bile duct stones with complex clearance of the bile duct is evaluated. Bile duct exploration and subsequent choledochojejunostomy (Roux-en-Y) was performed in 43 patients (median age 67 years) in the period 1976-82. There was no mortality and only one patient had a major complication. Twenty patients died during follow-up (median follow-up period 5 years); the median follow-up period for the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Before the availability of EST, CJS was performed for choledocholithiasis 66 . More than a decade ago, CJS was not commonly selected as a treatment option for choledocholithiasis because: (i) endoscopic cannot be performed when anastomotic stenosis has occurred and (2) surgical techniques are complicated 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Before the availability of EST, CJS was performed for choledocholithiasis 66 . More than a decade ago, CJS was not commonly selected as a treatment option for choledocholithiasis because: (i) endoscopic cannot be performed when anastomotic stenosis has occurred and (2) surgical techniques are complicated 3 .…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2) are favored methods of biliary enteric anastomosis [1]. About 98 % good results in patients followed up for 8 years have been recommended [11]. There is reluctance on the part of many experienced surgeons to perform side-to-side choledochoduodenostomy for fear that the flow of partly digested food might cause ascending cholangitis, but long-term follow-up in patients who have undergone this type of anastomosis does not provide justification for this fear [12].…”
Section: Discussionmentioning
confidence: 99%
“…In a series from the area of open surgery for CBD stones, we showed that a choledochojejunostomy, as the final solution for complicated CBD stones, was successful in 98% even after 8 years of follow-up [15]. These procedures can now also be performed laparoscopically, as mentioned before.…”
mentioning
confidence: 85%